Characterization of auxin transporter AUX, PIN and PILS gene families in pineapple and evaluation of expression profiles during reproductive development and under abiotic stresses - Zhao,Heming; Maokai,Yan; Cheng,Han; Guo,Mingliang; Liu,Yanhui; Wang,Lulu; Chao,Shi; Zhang,Minqian; Lai,Linyi; Qin,Yuan (PeerJ, 2021)
Polar auxin transport in plant is mediated by influx and efflux transporters, which are encoded by AUX/LAX, PIN and PILS genes, respectively. The auxin transporter gene families have been characterized in several species from monocots and eudicots. However, a genome-wide overview of auxin transporter gene families in pineapple is not yet available. In this study, we identified a total of threeAcAUX genes, 12 AcPIN genes, and seven AcPILS genes in the pineapple genome, which were variably located on 15 chromosomes. The exon-intron structure of these genes and properties of deduced proteins were relatively conserved within the same family. Most protein motifs were widespread in the AUX, PIN or PILS proteins, whereas a few motifs were absent in only one or two proteins. Analysis of the expression profiles of these genes elucidated that several genes exhibited either preferential or tissue-specific expression patterns in vegetative and/or reproductive tissues. AcAUX2 was specifically expressed in the early developmental ovules, while AcPIN1b and AcPILS2 were strongly expressed in stamens and ovules. AcPIN9b, AcPILS1, AcPILS6a, 6b and 6c were abundantly expressed in stamens. Furthermore, qRT-PCR results showed that several genes in these families were responsive to various abiotic stresses. Comparative analysis indicated that the genes with close evolutionary relationships among pineapple, rice and Arabidopsis exhibited similar expression patterns. Overexpression of the AcAUX1 in Arabidopsis rescued the phenotype in aux1-T, and resulted in increased lateral roots in WT. These results will provide new insights into auxin transporter genes of pineapple and facilitate our understanding of their roles in pineapple growth and development.
Keywords: Pineapple (Ananas comosus L.); Auxin transporter; Gene family; Expression profile; Reproductive development; Abiotic stresses